Fecal Calprotectin in Combination With Standard Blood Tests in the Diagnosis of Inflammatory Bowel Disease in Children - Ho, Shaun S. C.; Ross, Michael; Keenan, Jacqueline I.; Day, Andrew S. (Frontiers in Pediatrics, 2021)
Introduction: Fecal calprotectin (FC) is a useful non-invasive screening test but elevated levels are not specific to inflammatory bowel disease (IBD). The study aimed to evaluate the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of FC alone or FC in combination with other standard blood tests in the diagnosis of IBD. Methods: Children aged <17 years who had FC (normal range <50 μg/g) measured and underwent endoscopy over 33 months in Christchurch, New Zealand were identified retrospectively (consecutive sampling). Medical records were reviewed for patient final diagnoses. Results: One hundred and two children were included; mean age was 12.3 years and 53 were male. Fifty-eight (57%) of the 102 children were diagnosed with IBD: 49 with Crohn's disease, eight with ulcerative colitis and one with IBD-unclassified. FC of 50 μg/g threshold provided a sensitivity of 96.6% [95% confident interval (CI) 88.3–99.4%] and PPV of 72.7% (95% CI 61.9–81.4%) in diagnosing IBD. Two children with IBD however were found to have FC <50 μg/g. Sensitivity in diagnosing IBD was further improved to 98.3% (95% CI 90.7–99.1%) when including FC >50 μg/g or elevated platelet count. Furthermore, PPVs in diagnosing IBD improved when FC at various thresholds was combined with either low albumin or high platelet count. Conclusion: Although FC alone is a useful screening test for IBD, a normal FC alone does not exclude IBD. Extending FC to include albumin or platelet count may improve sensitivity, specificity, PPV and NPV in diagnosing IBD. However, prospective studies are required to validate this conclusion.